2017
DOI: 10.3389/fpls.2017.01280
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Water Productivity Responses to Irrigation Cut-off Strategies after Fruit Set Using Stem Water Potential Thresholds in a Super-High Density Olive Orchard

Abstract: An increase in the land area dedicated to super-high density olive orchards has occurred in Chile in recent years. Such modern orchards have high irrigation requirements, and optimizing water use is a priority. Moreover, this region presents low water availability, which makes necessary to establish irrigation strategies to improve water productivity. An experiment was conducted during four consecutive growing seasons (2010–2011 to 2013–2014) to evaluate the responses of yield and water productivity to irrigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 59 publications
6
35
0
2
Order By: Relevance
“…Differences in yield were associated to canopy volume since there were no differences in canopy productivity among treatments (Table ), neither in fruit fresh weight (Table ). It was previously reported that yield was not affected by light water stress, Ψ of −3.5 MPa, after fruit set; however, it is reduced with an intense water stress, Ψ of −5 MPa, after fruit set (Ahumada‐Orellana et al, ).…”
Section: Resultsmentioning
confidence: 95%
“…Differences in yield were associated to canopy volume since there were no differences in canopy productivity among treatments (Table ), neither in fruit fresh weight (Table ). It was previously reported that yield was not affected by light water stress, Ψ of −3.5 MPa, after fruit set; however, it is reduced with an intense water stress, Ψ of −5 MPa, after fruit set (Ahumada‐Orellana et al, ).…”
Section: Resultsmentioning
confidence: 95%
“…The values of Ψ leaf reached values of −4.75 to −4.45 MPa. Such declines of leaf water potentials were observed by several authors, even in irrigated olive orchards [3,9,12,14,50]. These authors observed that seasonal dynamics of plant water status respond to the variations in tree water status, the soil moisture conditions, and the atmospheric evaporative demand.…”
Section: Discussionmentioning
confidence: 72%
“…Some uncertainties were evoked on the threshold of Ψ leaf and the use of leaf potential to estimate the crop water status. Martin-Vertedor et al [3] and Ahumada Orellana et al [9] recommended the measure of stem potential at midday (Ψ stem ), which is more precise for irrigated mature olive orchards, less sensitive to the atmospheric changes, and gives more stable values so that it should be preferred to Ψ leaf .…”
Section: Discussionmentioning
confidence: 99%
“…Due to insufficient rainfall, irrigation is needed by olive tree orchards because it helps to increase olive fruit yield as well as its oil quality (Ramos and Santos, 2010). Findings of four harvest years, evidenced that yields are not significantly influenced if irrigation is stopped from fruit set (20 days after full bloom) until a Ψ stem threshold level of -3.5 MPa, whereas olive oil content and its composition were significantly influenced if Ψ stem thresholds of -5.0 (T3) and -6.0 (T4) MPa (Ahumada-Orellana et al, 2017). Studies on Moroccan Picholine cultivar demonstrated that olive trees in which 100% of the evapotranspirated water was furnished to the two sides of the root zone system of plants had a significantly lower production instead of plants in which water was furnished only in a section of the root zone system (Aganchich et al, 2008).…”
Section: Irrigation Of Olive Treesmentioning
confidence: 98%